A novel damage characterization approach for laminated composites in the absence of material and structural information. (September 2020) - Cao, Maosen; Su, Zhongqing; Xu, Hao; Radzieński, Maciej; Xu, Wei; Ostachowicz, Wiesław
Highlights: We propose a novel approach for identification of damage in laminated composites. A damage index is established using the damage-caused force. The damage index is in no need of prior material and structural information. The damage index can characterize the presence, location, and size of damage. The approach is experimentally validated by non-contact laser measurement. Abstract: Laminated composites have been increasingly used in structural components. However, transverse impact to a composite laminate can cause initial damage such as notches and delamination, jeopardizing the integrity and safety of composite laminated structures. With this concern, this study proposes a novel damage characterization approach for the identification of initial damage in composite laminates, even in the absence of material and structural information. In particular, starting from the vibration equation of composite laminates, a novel concept of damage-caused force is formulated to characterize damage, and strategies of isotropization and normalization are further integrated to deal with the absence of material and structural information. Thereby, a baseline-free damage index is established using the damage-caused force, by which the presence, location, and size of initial damage in cross-ply composite laminates can be characterized without knowledge of material and structural parameters. The capability of the approach is numerically verified on carbon fiber-reinforced polymer (CFRP) laminates with a notch and a delamination, respectively. The applicability of the approach is experimentally validated by identifying a notch and a delamination in CFRP laminates, respectively. The CFRP laminates are excited by lead-zirconate-titanate (PZT) actuators and scanned by a scanning laser vibrometer (SLV) to acquire high-resolution mode shapes. Numerical and experimental results show that the proposed approach features high robustness to environmental noise and is capable of identifying initial damage in cross-ply composite laminates without prior material and structural information.